Restabelecimento funcional do tendão extensor digital longo submetido a implante de enxerto jugular homólogo pós-ressecção parcial em equinos - Hussni, Carlos Alberto [UNESP]; Ferreira, Paloma Távora [UNESP]; Barbosa, Luciano [UNESP]; Watanabe, Marcos Jun [UNESP]; Rodrigues, Celso Antonio [UNESP]; Alves, Ana Liz Garcia [UNESP] (My University, 2014)
The functional restoration of the equine long digital extensor tendon after partial tenectomy was studied comparing one group submitted to homologous jugular graft (GE) and other group without graft used as control (GC). The animals were submitted to partial resection of the long digital extensor tendon with skin excision, followed by jugular graft suture in the GE. The wounds were treated by second intention and the limbs were supported with a bandage and cast. The horses were stall confined and monitored daily for lameness, wound tendon healing (planimetry and ultrasonography evaluation), limb functional restoration and cast sores. The repair tissue showed initial vascularization and developed granulation tissue. Three horses from GC had exuberant granulation tissue. The tendon functional restoration time from GE was significant less (average time of 28.3 days) than GC (45.9 days). The planimetry was significant different at 10 and 20 days, but it was similar at the final of experiment. Ultrasonographic exams showed the newly formed tendon tissue surrounding the implanted grafts with obvious circulatory activity, however with less organization comparing to the previous tendon before the lesion. Incorporation of a homologous jugular graft improved the quality of the repair tissue in equine extensor tendons avoiding the exuberant granulation tissue development and reduced tendon functional restoration time.
Functional restoration of the equine long digital extensor tendon submitted to homologous jugular graft after partial tenectomy
Keywords: Digital extensor tendon; Funccional restoration; Glutaraldehyde; Graft; Horses